Debris Extrusion Using Reciproc Blue and XP Endo Shaper Systems in Root Canal Retreatment. (24th March 2021) - AlOmari, Taher; Mustafa, Ruba; Al-Fodeh, Rami; El-Farraj, Hamza; Khaled, Waheeb; Jamleh, Ahmed
Abstract : This study aimed at assessing the performance of Reciproc Blue (RB) and XP Endo Shaper (XPS), used for canal retreatment on extracted teeth, in terms of debris extrusion and obturating materials removal. Thirty mandibular premolars were prepared to ProTaper X2 file, obturated using warm vertical compaction, and then incubated for 28 days at 100% humidity at 37°C. Teeth were randomly assigned into two groups, according to the system used for retreatment (RB and XPS). During retreatment, debris extruded beyond the apex was collected in preweighed Eppendorf tubes, and the retreatment time was measured. Afterward, the teeth were longitudinally sectioned to assess the remaining obturating materials. Data were statistically analyzed using the Mann–Whitney test and chi-square test at a 95% confidence level. All the samples had extruded debris at varying weights ranging from 0.125 mg to 3.680 mg. XPS extruded less debris than RB, but no difference was detected (Mann–Whitney test; P > 0.05 ). RB and XPS required 54.9 ± 17.9 and 22.3 ± 9.3 seconds to perform retreatment procedures, respectively (Mann–Whitney test; P < 0.05 ). The sealer was found in all the samples. Compared to the RB group, fewer samples with remaining gutta-percha were found in the XPS group (Chi-square test; P < 0.05 ). None of the files fractured during the retreatment procedure. The tested files appear to extrude debris beyond the apex. Although XPS was able to remove the gutta-percha completely from the majority of the canals, it was unable to remove the sealer.